2020
DOI: 10.1002/jdd.12438
|View full text |Cite
|
Sign up to set email alerts
|

Teaching methodologies for improving dental students’ implementation of ergonomic operator and patient positioning

Abstract: The aim of this study was to determine the impact of inter-professional teaching on the application of ergonomic operator and patient positioning. A randomized case-control study was conducted with 83 first-year dental students at the UNC Chapel Hill Adams School of Dentistry. Forty-nine percent (n=41) of the students solicited participated. All students participated in a didactic lecture on ergonomics, along with a pre-clinical practice session with peer patients. During the clinical practice session students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(95 reference statements)
0
6
0
1
Order By: Relevance
“…Regarding the postural awareness of dental students, observations and interviews have established that their knowledge can be improved and that better awareness of proper posture during patient care can help to reduce the risk of MSD [ 37 ]. In addition, Faust et al [ 38 ] demonstrated that the hands-on teaching of trained dental educators positively influences adherence to ergonomic principles. Three months after ergonomic training, 49% of the participating dental students reported a reduction in musculoskeletal pain [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the postural awareness of dental students, observations and interviews have established that their knowledge can be improved and that better awareness of proper posture during patient care can help to reduce the risk of MSD [ 37 ]. In addition, Faust et al [ 38 ] demonstrated that the hands-on teaching of trained dental educators positively influences adherence to ergonomic principles. Three months after ergonomic training, 49% of the participating dental students reported a reduction in musculoskeletal pain [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attrition bias was low in all studies but one. 31 All studies had a low risk of reporting bias. These other sources of bias included undefined prior ergonomic training to participants being uneven, variability in the equipment used, and lack of standardization in the positioning of test equipment (such as by make and model of dental chair and stool) on participants.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that WMSs are frequently seen in the practice of the dental profession with the effect of work-related and other environmental factors [ 24 , 25 ]. The reasons why WMSs are seen more frequently in dental students are the difficulty of the education and training process, intensive theoretical and practical training and exams, and being inexperienced compared to a dental professional [ 26 ]. Since it is very important to manage WMSs well and to determine the factors in order for individuals to fulfill their duties effectively, it is also necessary to consider this situation in dental students.…”
Section: Discussionmentioning
confidence: 99%